Xerostomia - A comprehensive review with a focus on mid-life health - Lisa Elizabeth Jacob; Meenakshi Krishnan; Anju Mathew; Anuna Laila Mathew; Tibin K Baby; Anand Krishnan (Wolters Kluwer Medknow Publications, 2022)
Xerostomia is defined as the subjective complaint of a dry mouth. Xerostomia is common in menopausal women owing to the hormonal changes which take place during midlife. Studies show a higher incidence of oral cancer in the postmenopausal period which substantiates the theory of estrogen deficiency in carcinogenesis. Radiotherapy in the treatment of these cancers can lead to oral dryness. Other etiological factors of xerostomia include systemic diseases commonly occurring in middle-aged individuals and xerogenic drugs. Saliva plays a pivotal role in the maintenance of oropharyngeal health and xerostomia can severely impair the quality of life. The aim of this review was to provide vital information pertaining to the etiology, signs, diagnosis, and treatment of xerostomia with an emphasis on midlife health. The articles for this review were obtained from PubMed Central, Google Scholar, EBSCO, Science Direct, Medknow, Scopus, EMBASE, Web of Science, and authorized textbooks published between 1988 and 2021.